Isolation, Identification and Quantification of Compounds with gastroprotective activity present in Centaurea solstitialis (Veterinary Science, 2017)
Centaurea solstitialis is a plant with antiulcerous properties. To isolate and identificate bioactive compounds responsible for the gastroprotective activity, phytochemist bioguided studies were carried out in flavonoids related with this pharmacological activity. A methanolic fraction, obtained from dried heads of the plant, was extracted with ethyl acetate previous hydrolysis with hydrochloric acid. Ethyl acetate fraction was chromatografhied in thin layer on plates of silica gel and the bands, that comigrated with authentic standards of quercetin (Rf = 0.80) and kaempferol (Rf = 0.89), became purified by HPLC, getting the isolating of the two flavonoids. The compounds were recovered and identified by mass spectrometry. Quantitative essays allowed to determine that the heads of the plant contain 0.63 and 1.47 mg of quercetin and kaempferol per gram of dry matter respectively
Keywords: Centaurea solstitialis